Optimalisasi Penggunaan Emis dalam Proses Pengolahan Data Madrasah Pada Seksi Pendidikan Madrasah (PENDMA) di Kementerian Agama Kabupaten Kediri - Aldien Ramadhan, Reffin; Nur Azizah, Umi; Nur'aini, Khusnadiah; Sukmawati, Anis; Rajanto, Sugeng Hari (Program Studi Manajemen Pendidikan Islam, 2024)
The use of the Madrasah Management Information System (EMIS) has become an integral part of the data processing process at the Kediri Regency Ministry of Religion. This research aims to optimize the use of EMIS in managing madrasa data. The research method involved data analysis, interviews and surveys conducted at a number of madrasas in Kediri Regency. The results of observations found that the implementation of EMIS at the Ministry of Religion in Kediri Regency was not optimal. Madrasah data does not correspond to real conditions and madrasah operators have difficulty operating EMIS because operators do not know the scheme for using EMIS correctly. This research suggests that madrasas consider the importance of EMIS data and complete the data on time to avoid delays in data collection.